Desain Didaktis Perkalian Menggunakan Papan Tulis Perkalian Dan Stick Es Krim - Syarif, Ahmad; Risnawati; Hamdani, M. Fikri (Global Action and Education for Society, 2026)
This study aims to identify learning obstacles, design didactic methods, implement didactic activities, and find changes after the retrospective stage. The method used is Didactical Design Research (DDR). The subjects of this study are second-grade elementary school students. Data were collected through observation during the learning process. The results showed that some students had difficulty understanding the concept of multiplication as repeated addition and demonstrated limitations in visualizing number patterns. To overcome these obstacles, concrete media in the form of multiplication boards and ice cream sticks were used. Ice cream sticks were used as manipulative tools to show groups of numbers, while multiplication boards helped students find multiplication patterns visually and structurally. The use of these two media made it easier for students to understand the basic concept of multiplication, especially for students with low numerical abilities. Significant changes occurred in concept exploration and number pattern comprehension activities. Students became more active and engaged in learning because the learning was concrete and contextual. These results indicate that the integration of multiplication boards and popsicle sticks in didactic design can improve the effectiveness of multiplication learning in elementary schools.